Detecting anomalies in large number of moving objects - He, Kelvin Zhenhao (2014)
The need of detection of patterns and behaviors has been increasing in demand in the recent years as the quantity of moving objects rises. Examples of moving objects can be vehicles, human beings, animals or even vessels. By acquiring the positions of moving objects and analyzing them, we can find out the behaviors of the subjects (moving objects).